Strengthening Quranic Literacy through Mentoring on the Yanbu’a Method at the TPQ in Panataban Village, Giri District, Banyuwangi Regency - Anyes Lathifatul Insaniyah; Moh. Kholip Beril Arahman; M. Faqih Azam Majid; M. Idrus Nur Zamzami; A. Irfan Afandi (Simfoni Ilmu Cindekia, 2026)
This community service initiative aims to strengthen Quranic literacy at the Panataban Village Quran Education Center (TPQ) by providing guidance on the implementation of the Yanbu’a method, focusing on the continuous improvement of teacher competence and students' reading abilities. Initial assessments revealed disparities in reading proficiency and a lack of standardized teaching practices at the local TPQ, necessitating a structured methodology and intensive support. The implementation team employed a Participatory Action Research (PAR) approach, encompassing collaborative problem identification, action planning, teacher training, instructional mentoring, observation and monitoring, and reflective evaluation for ongoing adjustments. Interventions targeted three key areas: teachers as agents of change, TPQ students as the primary beneficiaries, and the TPQ institution itself to ensure the institutionalization of the Yanbu’a method. Results indicate improvements in students' technical Quranic reading skills—specifically regarding fluency and adherence to *tajwid* (recitation rules)—and enhanced teacher capabilities, resulting in more consistent and confident instruction using the Yanbu’a method. Institutionally, the program successfully established a foundation for standardized Quranic instruction at the Panataban TPQ and developed sustainability strategies—including internal monitoring, simplified financial management, and community engagement—to ensure the program's independence beyond the mentoring period. Recommendations include adopting Yanbu’a as the permanent curriculum, strengthening internal monitoring systems, and providing training in institutional financial management to sustain and expand these positive impacts in the future.